Enhancing the effectiveness of infectious disease health education for children and adolescents in China: a national multicenter school-based trial - Xinxin Wang; Jieyu Liu; Yu Wu; Binbin Su; Manman Chen; Qi Ma; Tao Ma; Li Chen; Yi Zhang; Yanhui Dong; Yi Song; Jun Ma (BMC Public Health, 2023)
Abstract Background Infectious diseases pose a significant risk to the health and well-being of children and adolescents, and can even be life-threatening. Thus, our study aimed to explore the effectiveness of health education based on the social-ecological model in improving the knowledge of infectious diseases among this vulnerable population. Methods This study was a school-based intervention conducted in seven Chinese provinces in 2013, involving a total of 26,591 children and adolescents in the intervention group and 24,327 in the control group. The intervention group received a comprehensive health intervention based on the social-ecological model (SEM) over six months, which included a supportive environment, health education on infectious diseases, guidance on self-monitoring infectious disease-related behaviors, and other measures. Data on infectious disease-related knowledge and other characteristics were collected through questionnaires. The main outcome measure will be the difference in the effectiveness of health education regarding infectious diseases in children and adolescents between baseline and post-intervention. A mixed-effects regression model was used to calculate the odds ratio (OR) and 95% confidence interval (95% CI) to assess the impact of infectious disease-related interventions on the participants. Results We utilized a socioecological model as the foundation for a six-month health education program on infectious diseases targeting children and adolescents in the intervention group. At the individual and community levels, the correct rate of health behavior related to infectious diseases in the intervention group was higher than that in the control group (P < 0.05), the ORs (95% CI) were 0.94 (0.90–0.99) and 0.94 (0.89–0.99), respectively. But the intervention effect was not significant at the interpersonal level. The intervention effect at the organizational level was obvious, with an increase in opportunities for children and adolescents to acquire knowledge of infectious diseases from courses and lectures, teachers, and doctors, (all P < 0.05), with the ORs (95% CI) of 0.92 (0.87–0.97) and 0.86 (0.83–0.94), respectively. However, there was no significant difference between the intervention group and the control group in school infectious disease health education policy. Conclusion Enhancing health education regarding infectious diseases is crucial in promoting comprehensive prevention and control measures among children and adolescents. Nevertheless, it remains imperative to reinforce health education on infectious diseases at the interpersonal and policy levels. This holds significant reference value for mitigating childhood infectious diseases in the post-COVID-19 era.